Perceived quality of physiotherapy services among informal caregivers of children with cerebral palsy in Ibadan, Nigeria (2015)
OBJECTIVE: Effective physiotherapy intervention for children with cerebral palsy (CP) requires that expectations of their caregivers be incorporated into treatment plans and strategies. This study explored the perceived Quality of Physiotherapy (QoP) for children with CP in Ibadan, Nigeria METHODS: This cross-sectional survey explored the perceived QoP using the SERVQUAL instrument among informal care givers of children with CP from two different healthcare facilities. Data was analysed using Mann Whiney U and Wilcoxon Signed Rank tests at p ⩽ 0.05. RESULTS: Fifty-three informal caregivers (50 females, 3 males) of children with CP (32 males, 21 females) were surveyed. Fourth-fifths (81.13%) of the caregivers perceived the QoP service for their children as poor. The highest negative and positive ranks were in the tangible and responsiveness dimensions of the SERVQUAL respectively. CONCLUSIONS: The study demonstrated that caregivers of children with CP perceived the quality of physiotherapy provided for their children as poor. This poor perception is related more to the tangible dimension of care. Strategies to improve care environment for children with CP and their informal caregivers should be implemented to engender satisfaction with care.